The production of anti-biotin antibodies and the comparison of their efficiency to that of avidin in enzyme-linked immunosorbent assays - O'Connell, Theresa (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1987.